A Review of the Sedative, Anti-anxiety and Immunosti-mulant Properties of Withania somnifera (L.) Dunal (Ashwagandha) - Xu, Tian; Cock, Ian E (Pharmacognosy Communications)
Background: Withania somnifera (L.) Dunal, commonly known as ashwagandha, is a small woody shrub whose roots are used traditionally to treat numerous diseases. It is particularly well known for its sedative, sleep-inducing and immunostimulant effects. Materials and Methods: We undertook an extensive search of reviews and primary scientific studies to identify therapeutic uses of W. somnifera and studies that have reported on the phytochemistry and validation of the traditional uses. This information was used to identify gaps in the current research that require further study. Results: Withania somnifera root preparations have widespread uses as sedatives and in the treatment of stress-related conditions. Additionally, there is extensive evidence of the use of W. somnifera to stimulate the immune system to protect against pathogenic disease. Numerous studies have examined the mechanisms of action, which are summarised herein. Conclusion: Despite the widespread usage of W. somnifera roots as a sedative and as an immunostimmulant, the mechanisms of action are not completely understood. Substantial further work is required into the therapeutic mechanism(s) of this useful traditional medicine.
Keywords: Ashwagandha; Solonaceae; Ashwaghandq; Ayuverda; immunomodulation; Sedative; GABA